2018
DOI: 10.1109/tnnls.2016.2615134
|View full text |Cite
|
Sign up to set email alerts
|

Online Optimization With Costly and Noisy Measurements Using Random Fourier Expansions

Abstract: Abstract-This paper analyzes DONE, an online optimization algorithm that iteratively minimizes an unknown function based on costly and noisy measurements. The algorithm maintains a surrogate of the unknown function in the form of a random Fourier expansion (RFE). The surrogate is updated whenever a new measurement is available, and then used to determine the next measurement point. The algorithm is comparable to Bayesian optimization algorithms, but its computational complexity per iteration does not depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…2 shows the measurement setup and the results of automatically tuning the OSBF using the DONE algorithm [4], and manual tuning, both averaged over ten measurements. Manual tuning was performed by a human expert by looking at the frequency response of an OSBF, averaged over ten measurements (to reduce the noise level).…”
Section: Measurementsmentioning
confidence: 99%
“…2 shows the measurement setup and the results of automatically tuning the OSBF using the DONE algorithm [4], and manual tuning, both averaged over ten measurements. Manual tuning was performed by a human expert by looking at the frequency response of an OSBF, averaged over ten measurements (to reduce the noise level).…”
Section: Measurementsmentioning
confidence: 99%
“…The maximum stroke of the MAL limits the maximum amplitudes of the modes, hence the exploration parameters and bounds for each mode should be carefully chosen. Previously, DONE has successfully been used in WFSL-AO OCT, light sheet microscopy, and simulations of an optical beam forming network [29,38,47]. It was shown that DONE outperforms other algorithms in residual wavefront error and convergence speed [29].…”
Section: Discussionmentioning
confidence: 99%
“…In order to perform the DONE model computations in near real-time, fast algorithms are necessary. We present an improved and faster implementation of the DONE algorithm [29,38] used to maximize the AO-OCT signal for human retinal imaging. The biggest difference between the DONE algorithm reported in [29] and the current work is a faster implementation that allows the exploration and the bounds for each aberration to be set independently.…”
Section: The Done Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The automatic tuning algorithm used in this paper contains several hyper-parameters that are explained and investigated in [17]. Their values as used in this paper are shown in Table II for the OSBF and OBFN tuning results.…”
Section: Appendix B Algorithm Settingsmentioning
confidence: 99%